Do futures benefit Indian coffee producers?. (27th February 2013) - Dey, Kushankur; Sivakumar, A.
Coffee futures market needs to be efficient to benefit the producers. This paper explores whether this market provides the environment of hedging. In addition, we examine informational efficiency in the futures to justify the criteria for adequacy of hedging. The study is significant as India has over five years of experience with coffee futures market in a software-enabled trading environment. We use modified Pantula principle in testing co-integration and perform weak exogeneity test to draw better inferences on efficiency. The first level analysis shows excessive basis risk with negative hedge-effectiveness. At a further level, findings seem to corroborate the results of first level analysis significantly. The paper establishes that coffee futures market does not satisfy the criteria of hedging and spot markets are efficient compared to the futures.